STUDY THE INFLUENCE OF CARDIOVASCULAR SYSTEM PATHOLOGY TO THE QUALITY OF LIFE - Khusainova Munira Alisherovna; Ortikova Sohiba Xamroyevna (Journal of new century innovations, 2023)
Goal. To study the features of the psychoemotional state of middle-aged patients with acute coronary syndrome (ACS) without st segment elevation in the period of 6 months after hospitalization. Material and methods. 101 patients with ACS without st segment elevation with non-obstructive coronary lesion were included. The groups were formed by gender: group 1 — 51 women, group 2 — 50 men. The average age of women is 50.5±4.7 years, men 46.7±6.8 years. Patients were distributed depending on the outcome of ACS without segment elevation: subgroup A — patients with unstable angina (NS), subgroup B — with myocardial infarction. The patients were interviewed by phone six months after discharge from the hospital. The questionnaire included the main indicators of health, emotional balance, physical activity, quality of life.